Subgrouping siblings of people with autism: Identifying the broader autism phenotype. Issue 6 (2nd September 2015) - Ruzich, Emily; Allison, Carrie; Smith, Paula; Watson, Peter; Auyeung, Bonnie; Ring, Howard; Baron‐Cohen, Simon
Abstract : We investigate the broader autism phenotype (BAP) in siblings of individuals with autism spectrum conditions (ASC). Autistic traits were measured in typical controls ( n = 2, 000), siblings ( n = 496), and volunteers with ASC ( n = 2, 322) using the Autism‐Spectrum Quotient (AQ), both self‐report and parent‐report versions. Using cluster analysis of AQ subscale scores, two sibling subgroups were identified for both males and females: a cluster of low‐scorers and a cluster of high‐scorers. Results show that while siblings as a group have intermediate levels of autistic traits compared to control individuals and participants with ASC, when examined on a cluster level, the low‐scoring sibling group is more similar to typical controls while the high‐scoring group is more similar to the ASC clinical group. Further investigation into the underlying genetic and epigenetic characteristics of these two subgroups will be informative in understanding autistic traits, both within the general population and in relation to those with a clinical diagnosis. Autism Res 2016, 9: 658–665 . © 2015 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research